The Evolution of Migration: The Case of Coastal Sandy Zone in Thua Thien Hue Province, Vietnam - Minh, Dao Duy; Lebailly, Philippe; Hao, Nguyen Dang; Hop, Ho Thi Minh (International Journal of Economics and Financial Issues, 2019)
By using the baseline data of Hao (2009) with 110 households, this study aimed to evaluate migration tendencies, reasons for migrations, contributions of migration and the factors affecting immigration waves. Two types of models were used, the Difference and Differences method applied to carry out the change of total income caused by the decision to migrate; the logistic models applied to identify the factors affecting on migration decision of household. The results showed that migration had a vital role in livelihood outcome and the positive trends in migration issues included diversification of jobs, higher level of education and higher wage for migrants. From the research findings and the problem statements, some well-orientated policies need to be focused on taking advantage of migration issues and reducing its negative impacts in the long term (Deshingkar, 2006; Paes Herrera et al., 2018). Keywords: Income Distribution; Wage; Migration JEL Classifications: D30, O15 DOI: https://doi.org/10.32479/ijefi.8134